"Spear and shield in one" nanochaperone enables protein to navigate multiple biological barriers for enhanced tumor synergistic therapy. (30th May 2022) - Zhang, Xiaoxiao; Wang, Da-Yuan; Wu, Xiaohui; Zhao, Yu; Li, Xue; Ma, Rujiang; Huang, Fan; Shi, Linqi
Abstract : A chaperone-mimicking nanocarrier was developed to achieve highly efficient intracellular delivery of protein and boost antitumor synergistic therapeutic effect in combination with small-molecule drugs. Abstract : Protein therapeutics have been viewed as powerful candidates for cancer treatment by virtue of highly specific bioactivity and minimized adverse effects. However, the intracellular delivery of protein drugs remains enormously challenging due to multiple successive biological barriers in vivo . Herein, a bioinspired nanochaperone is developed to assist proteins in vanquishing the sequential physiological barriers in a holistic manner and enhance synergistic tumor therapy. By concurrently mimicking the N-terminal-binding domain and C-terminal-stabilizing domain of natural chaperones, this nanochaperone can efficiently capture the protein by multiple interactions and hide them in the confined spaces on the surface, serving as a shield to resist enzymatic degradation and avoid immune clearance during blood circulation. Upon reaching the tumor site, the nanochaperone rapidly responds to the acidic tumor microenvironment and turns into partial protonation, acting as a spear to facilitate tumor cellular internalization. More importantly, further protonation of nanochaperone in the lysosome of tumor cells enables it to blast the lysosome and achieve cytosolic protein delivery with reserved bioactivities. Furthermore, this nanochaperone-based protein transduction strategy is demonstrated to combine with small-molecule drugs to synergistically amplify the anti-tumor therapeutic effect in vitro and in vivo, providing a potential platform for the exploitation of diverse combinations of anti-tumor therapies.